Experimental investigation of impact damage on repetitive loading tolerance in metal-fiber multilayers - Hasani Monfared, Banan; Sedaghat, Alireza (International Journal of Engineering and Technology, 2019)
Fiber is not sensitive to fatigue in some fiber-metal multilayers. They leave a large part of the load through the cracks and prevent the crack from opening. Due to this prevention, the opening in GLARE is less than that of the metals. Unlike what is observed in metals, concentration factor of crack tip is not fully influenced by increase in crack length. Hence, this study uses the experimental method to examine post-impact fatigue behavior of glass fiber-reinforced metal composites, known as GLARE. The GLARE made in this study was produced by autoclave in three types of GLARE 1.2-3, GLARE 1.2-4 and GLARE 3.2-5 and was exposed to impact test by different forces and then fatigue test with different cycles. The results were studied. The results showed that the first GLARE 1.2-3 specimen was completely pierced after the impact test. The second GLARE 1.2-3 specimen produced fatigue cracks from impact dent in the only aluminum impacted layer. These cracks were then amplified to the edge of the specimen. Both GLARE 1.2-4 specimens showed approximately equal fatigue life. The first GLARE 1.2-4 specimen failed near the radius due to the disturbing cracks in a way that is common in FML specimen. Moreover, both GLARE 1.2-4 specimens exhibited cracking in both aluminum layers. In 1.2-5 GLARE, both specimens showed a decrease in fatigue life and increase in impact energy.Â Â